The Institution of Slavery in British Colonial America - Garcia Delgado, Ana Karen (The Toro Historical Review, 2020)
In the mainland British American colonies, slavery as an institution evolved throughout the seventeenth to the eighteenth century. The colonies transformed from “societies with slaves” to “slave societies.” Along with the transformation to slave societies, the labor of slaves also changed. Analyzing Historical Statics to evaluate the demographics, the economy of the colonies, and the legal structure will aid in understanding the changes in the institution of slavery.